Sustainability Accounting Adoption: The Impact of ESG Dimensions on Managerial Decision-Making - Albertus Karjono; Edi Wahyu Wibowo; Bambang Wahyudi Wicaksono (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Contemporary developments in corporate management reveal an increasing emphasis on sustainability manifested through Environmental, Social, and Governance (ESG) initiatives and digitalization as key determinants of financial performance and firm value. This literature review aims to analyze the complex and dynamic interplay between corporate sustainability and digital disruption, as well as their impact on corporate financial performance and firm value. The analysis is based on a review of studies within the accounting and finance domains that predominantly employ quantitative approaches. Common methodologies found in the reviewed research include longitudinal panel econometric models and Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were sourced from secondary datasets, such as global financial databases and corporate annual reports. Key variables were measured using both accounting perspectives (Return on Assets) and market perspectives (Market Value to Book Value) to assess financial performance and firm value. The findings support a positive and significant relationship between sustainability performance and financial performance, as measured by both ROA and MV/BV. High-quality environmental accounting disclosure is significantly associated with a lower cost of equity, indicating that investors prioritize sustainability factors in their investment decisions. Digital disruption and financial technology (FinTech) act as transformative forces. FinTech exerts a strong, positive, and significant direct impact on the adoption of sustainable finance practices and enhances the integration of ESG into financial reporting (FRESGI). Digital transformation was found to positively moderate the relationship between financial performance (ROA) and business sustainability, thereby reinforcing the positive effect. However, cross-sector interactions involving corporate sustainability and public sector financial or technological agendas can exert a negative moderating effect on ESG integration, suggesting structural friction or a misalignment of priorities.